2018
DOI: 10.1016/j.apcata.2018.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the 1-butanol productivity in the ethanol condensation catalyzed by noble metal nanoparticles supported on Mg-Al mixed oxide

Abstract: The role of the addition of a noble metal (Ru and Pd) on the surface of a basic mixed oxide (MgAl) used as ethanol condensation catalyst is studied in this work. The activity trends for all the reaction steps (dehydrogenation, condensation, dehydration, and hydrogenation) were analyzed, concluding that dehydrogenation step is the rate-determining one under inert conditions whereas hydrogenations also take a relevant role under reducing conditions. Ruthenium has shown very promising 1-butanol productivities at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…And intramolecular dehydration of 1-butanol could lead to the formation of 1-butylene, which could be further hydrogenated to produce butane (step (8 and 9)). In addition, ethanol can convert to carbon monoxide, carbon dioxide or C 1 -C 3 products through oxidation or hydration (step (10)) [38][39][40], while carbon monoxide/dioxide can also be formed from acetaldehyde decarbonylation [41,42] or from organic acids (in-situ generated) decarboxylation [43]. Additionally, intermolecular dehydration can undergo at relatively low temperatures (<623 K) to form ethyl ether (step (11)) over zeolite-based catalysts between two molecules of ethanol.…”
Section: C-c Bond Formation Pathwaymentioning
confidence: 99%
“…And intramolecular dehydration of 1-butanol could lead to the formation of 1-butylene, which could be further hydrogenated to produce butane (step (8 and 9)). In addition, ethanol can convert to carbon monoxide, carbon dioxide or C 1 -C 3 products through oxidation or hydration (step (10)) [38][39][40], while carbon monoxide/dioxide can also be formed from acetaldehyde decarbonylation [41,42] or from organic acids (in-situ generated) decarboxylation [43]. Additionally, intermolecular dehydration can undergo at relatively low temperatures (<623 K) to form ethyl ether (step (11)) over zeolite-based catalysts between two molecules of ethanol.…”
Section: C-c Bond Formation Pathwaymentioning
confidence: 99%
“…The Guerbet reaction of alcohols requires the dehydrogenation of the alcohol to the reactive aldehyde [38,39], a reaction that can be viewed as the microscopic reverse of the hydrogenation of an aldehyde to an alcohol. Moreover, one of the main pathways to selectivity losses during the Guerbet reaction is the C-C bond cleavage of acetaldehyde via decarbonylation [40]. Comparison of monometallic and bimetallic Pd-based catalysts showed that adding Cu to Pd significantly altered the product distribution, shifting selectivity to the hydrogenation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The Guerbet reaction of alcohols requires the dehydrogenation of the alcohol to the reactive aldehyde [38,39], a reaction that can be viewed as the microscopic reverse of the hydrogenation of an aldehyde to an alcohol. Moreover, one of the main pathways to selectivity losses during the Guerbet reaction is the C-C bond cleavage of acetaldehyde via decarbonylation [40].…”
Section: Resultsmentioning
confidence: 99%